Hubungan Pengetahuan dan Sikap Dengan Tindakan Seksual Pranikah Remaja Di SMA Kabupaten Sijunjung - Elda Yusefni (Poltekkes Kemenkes Padang, 2017)
Premarital sexual behavior has a negative impact that unwanted pregnancy and abortion. Based on data found BKKBN and secondary school students had sexual intercourse 63% and 21% had an abortion. The aim of research to determine the relationship of knowledge and attitudes to premarital sexual acts Sijunjung teenagers in high school. This type of research analytic survey with the cross-sectional approach. The study was conducted in January-September 2013 in class X SMA N 9 Sijunjung on 65 samples using questionnaires, the data processed using univariate and bivariate frequency distribution by chi-square test. The data is processed by a computerized system. The results showed a minority of students (38.5%) had a high-risk sexual activity before marriage. A small portion (33.8%) students had low knowledge levels, the vast majority (63.1%) students had negative attitudes toward premarital sexual. There is a significant relationship between knowledge and attitudes to premarital sexual activity in adolescents. Based on the research results suggested in the school make reproductive health education programs for adolescents in collaboration with health care, providing information about the dangers of premarital sex among adolescents, spiritual counseling or held ESQ activities every student or a new student.